Identifikasi Sistem Budidaya, Pemanfaatan dan Analisis Nutrisi Sayur Hitam (Rungia Klossii) Asal Distrik Mapia Kabupaten Dogiyai - Desi Natalia Edowai; Ivonne Fitria Mariay (Fakultas Pertanian Universitas Papua, 2017)
The objective of this research is to identify the farming systems and the utilization of sayur hitam (Rungia klossii) by the Mee tribe in the Regency of Dogiyai as well as to provide information about the nutrients in the R. klossii. Descriptive method with direct observation is used in the field to examine the farming system and crop nutrient content. Analytical procedures were implemented using Gravimetry and atomic absorption spectrophotometry. The analysis were conducted in the Laboratory of Chemistry, Faculty of Science, University of Papua on April 2016. The variables observed by those methods include the identification of farming systems and the crop nutrient content in the leaves. Farming systems applied by the community to cultivate Rungia klosii is a mixed farming systems based on local knowledge. Based on the analysis of the nutrient content of Rungia klossii in terms of water content, oil content of fat, iron levels, manganese content, the levels of calcium and magnesium levels, the magnesium levels in Rungia klosii is 272.0892 mg/L which is the highest.